INSIGHT (Staff): Prison Healthcare Professionals’ Attitude to Medical Student Psychiatry Placements and Understanding of Social Determinants of Health - Sadia Nafees; Arthur Jones; Andrea Taylor-Clutton; Justin Lawson; Rob Poole (BJPsych Open)
Aims: The Social Determinants of Health (SDOH) are generally taught as epidemiological facts rather than clinically relevant context. Psychiatry placements at HMP Berwyn (INSIGHT) provide medical students with exposure to SDOH at an individual level, allowing them to learn about the unique challenges faced by both the inmates and clinicians.